Fire and ice a novel - Garwood, Julie (New York : Ballantine Books, 2008)
The daughter of notorious, high-profile thief Bobby Rose, journalist Sophie Rose leaves her job at a major Chicago newspaper for a small local paper, but when she stumbles into the middle of a bizarre story, she follows the trail of the mystery north to Prudhoe Bay, Alaska, accompanied by a bodyguard, Jack Prescott, a sexy FBI agent.
Keywords: Journalists -- Fiction; Bodyguards -- Fiction; Chicago (Ill.) -- Fiction; Prudhoe Bay (Alaska) -- Fiction; Love stories